Strategi Komunikasi Dosen dan Mahasiswa Dalam Penggunaan AI pada Pembelajaran Daring - Marina Yuliani; M Hanif Fatahillah Iskandar; Mega Mutia Maeskina (Jurnal Inovasi Komunikasi, 2026)
Abstrak. Artificial Intelligence growth have brought about significant changes in online learning at the university level. This study aims to understand the communication strategies employed by instructors and students in the use of AI during the online learning process. This study employs a qualitative phenomenological approach that explores the subjective experiences of participants who support AI as a medium for online learning. Interviews were conducted with students and faculty members who actively use AI platforms such as Canva Magic Write, ChatGPT, and Grammarly. The results indicate that the communication strategies established between faculty and students are collaborative, adaptive, and open to technological advancements, as they must align with the evolving times. However, challenges exist, including dependency, academic ethics, and disparities among AI users. In the digital age, this study is expected to serve as a foundation for developing more reflective, adaptive, and humanistic educational communication strategies.